2020
DOI: 10.1590/1981-6723.23019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prochilodus lineatus meat for burger making

Abstract: The study aimed to elaborate burgers with fillet and pulp (fish carcass meat) of grumatã (Prochilodus lineatus), and to evaluate its centesimal composition, microbiological and sensorial properties. Three formulations were prepared. One was prepared with the fillet (0% pulp), and the remaining two contained 15% or 30% pulp (instead of fillet), textured soy protein, wheat flour and condiments. The centesimal and microbiological composition was evaluated in pre-ready burgers. For sensory analysis, the burgers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, hamburger formulations based on salmon fillet showed higher protein (18.1%–19.7%) and lipid (11.0%), and lower ash (1.4% to 1.6%) and moisture contents (60.0%) (Cilli et al, 2020). Pretto et al (2020) also reported higher fat content of fish burgers containing pulp and fillet from grumatã. Thus, these differences in the proximate constitution of fish burgers shown in different studies are related to the composition of the fish and other ingredients used in the formulations.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, hamburger formulations based on salmon fillet showed higher protein (18.1%–19.7%) and lipid (11.0%), and lower ash (1.4% to 1.6%) and moisture contents (60.0%) (Cilli et al, 2020). Pretto et al (2020) also reported higher fat content of fish burgers containing pulp and fillet from grumatã. Thus, these differences in the proximate constitution of fish burgers shown in different studies are related to the composition of the fish and other ingredients used in the formulations.…”
Section: Resultsmentioning
confidence: 91%
“…Panga fillets ( Pangasius hypophthalmus ) were purchased at the local market (Uruguaiana City, Rio Grande do Sul state, Brazil) and used for the preparation of fish burgers. Five formulations of fish burgers were prepared based on Pretto et al (2020) with modifications as follows: a control formulation (without the addition of micronized yerba mate – MYM) and four formulations were added with 0.5%, 1.0%, 1.5%, and 2.0% of MYM. In addition to panga fillets (83.7%) and MYM, textured soy protein (4.0%), wheat flour (5.0%), black pepper (0.5%), garlic paste (1.0%), dried spices (4.5%), and salt (1.3%) were used.…”
Section: Methodsmentioning
confidence: 99%